Checklist and key for the identification of fish fauna of the uberaba river, upper paraná river system, Brazil - Ribeiro, Douglas de Castro [UNESP]; Chagas, Jumma Miranda Araújo [UNESP]; Thereza, Mariana Ribeiro [UNESP]; Langeani, Francisco [UNESP] (Pensoft Publishers, 2019)
The Uberaba River is an important right-bank tributary to the Grande River, in the Upper Paraná River system, Brazil, and the main water source for the public supply of the Uberaba city, Minas Gerais state. An inventory, an identification key, and photographs of the fish species of the Uberaba River are provided, based on samples made between 2012 and 2014 at 14 sampling sites in the river system. A total of 73 species was recorded from six orders, 20 families, and 49 genera. Characiformes and Siluriformes are the most speciose orders and Characidae and Loricariidae are the most commonly recorded families. Most species are autochthonous, nine are considered allochthonous, and two species are exotic. The Uberaba River has a diverse and heterogeneous ichthyofauna, typical of rheophilic environments, with endemic species and few non-native species.
Keywords: Brazilian Cerrado; Freshwater fish; Neotropical Region; Rheophilic environment; Threatened species